Review: land, cloud, and climate change (in focus: Borneo) - Jason Pajimola Punay; Ratri Andinisari (Journal of Infrastructure Planning and Engineering, 2022)
This article discusses the salient findings of the Intergovernmental Panel on Climate Change Special Report on Climate Change and Land (2019). Local impacts of global warming in Borneo are discussed in terms of changes in temperature and precipitation. A drier and warmer climate is expected with the continued deforestation of Borneo. Changes in land surface characteristics of Borneo also affect the properties of cloud that forms over it. Deforested areas are generally associated with diffused clouds, small cloud particles, and thin and high clouds. Low vegetative areas are associated with a low evapotranspiration rate and low amount of latent heat release, which discourages the formation of convective clouds. The weak updraft associated with a non-convective cloud cannot support the formation of large cloud droplets. Moreover, the deforestation of primary forests of Borneo and replacing them with palm trees may cause larger cloud properties’ variability over the area.